COGNITIVE COMPETENCIES OF SECONDARY SCHOOL TEACHERS IN JORDAN FROM THEIR POINT OF VIEW - AL-Momani, Mohammad Omar; Alrabadi, Insaf George (Sanata Dharma University Yogyakarta, 2022)
The study aimed to identify the level of cognitive competencies for secondary school teachers in Jordan from the teachers’ point of view and their relationship to gender and educational qualification variables. The descriptive approach was used, and the study sample consisted of (210) male and female teachers in the first semester of the academic year (2021-2022), in addition to using the questionnaire as a study tool. The study concluded that the level of cognitive competencies for secondary school teachers in Jordan was high, as the percentage of response to it reached (76.4%). . The results also showed that there were no statistically significant differences in the cognitive competencies according to the gender variable (males, females), in addition to the presence of statistically significant differences in the cognitive competencies of teachers according to the educational qualification variable and in favor of graduate degree holders (Masters and Ph.D.).